Evaluating Internal and External Data Points in Long-term Periodical Testing with Protection Relays - Aldhaher, Hind (My University, 2022)
A protection relay is a part of the electrical network intended to protect the distribution network and react in case of abnormal situations. The protection relay can be electromechanical, static, microprocessor-based, or digital, also known as numerical. The numerical protection relay is the newest type of protection relays, which uses a digital signal processor. With the modernization of protection relays, various failures inside the protection relays are nowadays becoming more challenging to detect. Therefore, new test methods need to be developed to detect protection relay’s failures and to test the functionality of protection relays. Continuous testing, quality assurance, and development of protection relay’s testing methods will reduce the failures may occur in protection relays. The purpose of this study is to reduce the failure situations of protection relays and to focus on ensuring and improving the quality of protection relays through their continuously expanding lifetime by performing a new test method, long-term testing, as a part of long-term test system. This study is carried out in collaboration with ABB Oy that is a major global technology company with operations in over 100 countries that specializes in automation and electrification. The first objective of this study is to conduct long-term testing with a protection relay called REX640 and to automate the entire testing process, which includes collecting, storing, and analyzing data programmatically. In this study data will be collected from internal and external data points of REX640. The research aims to discover the relevant data in long-term periodical testing with protection relays to evaluate the prediction of protection relay failures. To discover the relevant data, the first research question is defined as follow: What data is relevant in long-term periodical testing with protection relays? A proper method should be discovered to collect the relevant data. The second objective of this study is to discover a method to evaluate, store, and analyze the collected protection relay data. This will allow protection relay failures to be detected. To find the proper method, the second research question is defined as follow: Which method will be used to collect the relevant data? The interviews, literature review, and automated test environment developed in this study allowed finding answers to the research questions. As a result, the study identified the relevant data in long-term periodical testing and a proper method to collect the identified relevant data. The relevant data and the discovered method will allow identifying the defects may occur in the protection relay and evaluating the predictability of protection relay failures with long-term periodical testing before a major disruption occurs in the distribution network.

Suojarele on sähköverkon osa, jonka tarkoituksena on suojata jakeluverkkoa ja reagoida poikkeustilanteissa. Suojarele voi olla sähkömekaaninen, staattinen, mikroprosessoripohjainen tai digitaalinen eli numeerinen. Numeerinen suojarele on uusin suojareletyyppi, jossa käytetään digitaalista signaaliprosessoria. Suojareleet kehittyvät nopeata vauhtia ja niiden nykyaikaistumisen myötä suojareleiden sisällä olevien erilaisten vikojen havaitseminen on nykyään entistä haastavampaa. Tämän vuoksi on kehitettävä uusia testausmenetelmiä suojareleiden sisäisten vikojen havaitsemiseksi sekä niiden toimivuuden testaamiseksi. Suojareleiden jatkuva testaus, laadunvarmistus ja kehittäminen vähentävät suojareleissä esiintyvien vikojen mahdollisuutta. Tutkimuksen tarkoituksena on vähentää suojareleiden vikatilanteita ja keskittyä varmistamaan ja parantamaan suojareleiden laatua niiden jatkuvasti pidentyvän käyttöiän aikana suorittamalla uutta testausmenetelmää, pitkäaikaistestausta osana pitkäaikaistes-tausjärjestelmää. Tämä tutkimus toteutetaan yhteistyössä ABB Oy:n kanssa. ABB on merkittävä maailmanlaajuinen teknologiayritys, jolla on toimintaa yli 100 maassa ja joka on erikoistunut automaatioon ja sähköistämiseen. Tutkimuksen yksi tavoite on suorittaa pitkäaikaista jaksottaista testausta ABB:n REX640-nimiselle suojareleelle ja automatisoida ohjelmallisesti kokonaista testausprosessia, johon sisältyy datan kerääminen, tallentaminen ja analysointi. Tutkimuksessa kerätään dataa REX640:n sisä- ja ulkopuolelta. Tutkimuksessa on selvitettävä pitkäaikaisen testauksen aikana asiaankuuluvaa dataa, jolla saadaan arvioitua suojareleen hajoamisen ennustamista. Asiaankuuluvan datan selvittämiseksi määriteltiin ensimmäinen tutkimuskysymys seuraavasti: Mikä data on relevantti pitkäaikaisessa jaksottaisessa testauksessa suojareleiden kanssa? Relevantin datan löytämiseksi, on selvitettävä menetelmä, jonka avulla voidaan kerätä kyseistä dataa. Näin ollen, tutkimuksen toinen tavoite on löytää menetelmä, jonka avulla arvioidaan, tallennettaan sekä analysoidaan suojareleestä kerättävää dataa. Sopivan menetelmän löytämiseksi määriteltiin toinen tutkimuskysymys seuraavasti: Mitä metodia tullaan käyttämään relevantin datan keräämiseksi? Tutkimuksessa kehitetyt haastattelut, kirjallisuuskatsaus, vaatimukset sekä automatisoitu testiympäristö auttoivat löytämään vastauksia tutkimuskysymyksiin. Tuloksena selvitettiin pitkäaikaiselle jaksottaiselle testaukselle relevanttia dataa sekä sopivaa metodia havaitun relevantin datan keräämiseksi. Relevantin datan sekä kehitetyn metodin avulla on mahdollisuus tunnistaa suojareleissä ilmeneviä vikoja sekä arvioida suojareleiden vikojen ennustettavuutta pitkäaikaisen jaksottaisen testauksen avulla ennen kuin jakeluverkossa tapahtuu merkittäviä häiriöitä.
Keywords: fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|